STRATEGI KOMUNIKASI AKUN INSTAGRAM RACHEL VENNYA DALAM KAMPANYE SOSIAL UNTUK MENINGKATKAN MINAT DONASI MILENIAL - Firdhaus, Annisa; Satria , Alfi; Sobirin (Journal of Islamic Studies, 2023)
The stratetgy of Rachel Vennya’social campaign on Instagram is measurement in the sense of achieving the goals or objectives that have been previously set by the Rachel Vennya social campaign which aims to increase interest in donations among millenials so that other circles follow and people in need can immediately receive asistance, especially for people who are sick or have symptoms of covid and other people who are affected by this covid-19, both physically and spiritually. Based on this, the following problems are formulated: (1) What is the strategy forusing instagram’s social meta by Rachel Vennya in attracting donations? (2) How effective is Rachel Vennya’s communication model on instagram in growing millenial donation interest on the Kitabisa.com fundraising platform?. This research is a qualitative research. The results showed that (1) the campaign strategy through rachel Vennya's Instagram social media by uploading photo and video posts, taking real action and updating about the distribution of donation funds to a predetermined place made researchers believe that the communication strategy carried out by rachel Vennya was successful by looking at the response of the people who are so sympathetic and enthusiastic to help donate and also disseminate information to donate to other communities. (2) the effectiveness of the campaign carried out by Rachel has proven to be effective because there is a percentage of 83.63% of the number of donors after seeing the post, and this is a very high percentage.